Enhancing Food Security In Rural Communities Through Implementation Of Hydroponic Technology - Lutfi Prastyo; Magaretha W. Syahputri; Nadia T. Nurhidayanti; Shella N.P. Supandi; Ranny L. Rumbiak; Naufal M. Akmal; Fadli Rozaq; Bambang Wahyu Nugroho (BAKTIMU : Jurnal Pengabdian Kepada Masyarakat, 2023)
Not all rural areas in Indonesia have fertile agricultural lands that are suitable for growing food crops, including vegetables. One of them is Dukuh Plampang II, Kalirejo Village in Kapanewon (Subdistrict) Kokap, Kulonprogo Regency, Special Region of Yogyakarta, the location of the Yogyakarta Muhammadiyah University Community Service Program (Kuliah Kerja Nyata – KKN) in Even Semester 2022/2023 Group 103. So far, the people of Dukuh Plampang II have met their needs for food, especially vegetables, by relying on supplies from mobile vegetable retailers. Besides having to spend a certain amount of money to buy vegetables, this dependence is also vulnerable to the risk of supply delays caused by one or another constraint. In the long term, this dependence can also reduce the level of food security. The purpose of the KKN activities at that location was formulated as an effort to increase food security with an effort to reduce dependence on external supplies such as mobile vegetable sellers. The form of technology introduced is vegetable farming using hydroponic facilities. This research uses the participatory social action research (Riset Transformasi Sosial Partisipatif – RTSP) method in the form of a participatory and transformative research approach that aims to bring about social change and overcome social problems through a collaborative and empowering process. This study examines the link between the main values of community empowerment in increasing the food security of rural communities by cultivating vegetables through hydroponic technology. Hydroponics is a method of cultivating vegetables by utilizing water without using soil as a nutrient medium. This research also shows that the use of hydroponic technology in growing vegetables can help rural communities maintain their food security. Hydroponic technology can also be used as an alternative for rural communities that have dry land and can also reduce the community's dependence on the supply of vegetables by mobile vegetable traders. Apart from that, the Women Farmers Group (Kelompok Wanita Tani – KWT) in the Dukuh Plampang II has the motivation to use hydroponic technology. Key Words: Food Security, Rural Communities, Hydroponic, Participatory Social Action Research